Advances in research to restore vision - Kun Do Rhee (Journal of Animal Reproduction and Biotechnology, 2023)
Mammalian eyes have a limited ability to regenerate once neurons degenerate. This results in visual impairment that impacts the quality of life among adult populations as well as in young children leading to lifelong consequences. Various therapies are in development to restore vision, and these include gene therapy, stem cell therapy, in-vivo transdifferentiation, and transplantation of a patient’s whole eye obtained from interspecies blastocyst complementation. This review discusses advances in the research as well as hurdles that need to be resolved to have a successful restoration of vision.